DEVELOPMENT, EVALUATION AND RP-HPLC METHOD FOR SIMULTANEOUS ESTIMATION OF QUERCETIN, ELLAGIC ACID AND KAEMPFEROL IN A POLYHERBAL FORMULATION - K., SHALINI; K., ILANGO (International Journal of Applied Pharmaceutics, 2021)
Objective: The current study was planned to develop polyherbal tablet formulation, standardization and evaluation for mitigating the symptoms of polycystic ovarian syndrome (PCOS). To control the issue of PCOS in women by the utilization of newly developed polyherbal tablet formulation. Methods: The polyherbal tablets were prepared using a hydroalcoholic extract of the selected medicinal plants viz. Asparagus racemosus, Bauhinia variegata, Caesalpinia bonducella, Saraca asoca, and Symplocos racemosa with the help of a super disintegrant addition technique using crospovidone, kyron T-314 and pregelatinized starch in various percentages. Evaluation assessments such as pre-formulation studies, weight variation, hardness, friability, thickness, disintegration, IR compatibility and simultaneous estimation of quercetin, ellagic acid and kaempferol by RP-HPLC method were done. Results: The results reveal that preformulation and evaluation parameters were satisfactory and found to be within an acceptable limit. The Fourier transform infrared spectroscopy (FTIR) compatibility displays no chemical interaction amongst the hydroalcoholic extract of polyherbal formulation and excipients. In simultaneous estimation, the retention time of quercetin, ellagic acid, and kaempferol were found to be 4.86, 6.96 and 10.01 min respectively. The linearity of quercetin, ellagic acid and kaempferol were found in the range of 0-200 µg/ml with correlation coefficients (R2>0.997) within the tested ranges. The LOD and LOQ values of quercetin, ellagic acid and kaempferol were found to be 11.86, 2.63, 5.28 µg/ml and 35.95, 7.98, 16.00 µg/ml respectively. The % RSD values were found to be less than 2 showed the optimized method is precise. Conclusion: To conclude, the prepared polyherbal tablet and its quality control analysis revealed satisfactory pharmaceutical properties that fulfill within the limits of pharmacopeial standards. The RP-HPLC method for simultaneous estimation of quercetin, ellagic acid and kaempferol were simple, precise, accurate and consistent for the quantitative analysis and quality control examination of herbal formulations.